A model for female South African investors' financial risk tolerance - Jessica Lawrenson; Zandri Dickason Koekemoer (Cogent Economics & Finance, 2020)
Research relating to the influence of investor's demographic factors and personality traits on financial risk tolerance receives increasing attention. Financial risk tolerance refers to the degree of uncertainty an investor is willing to bear, with regards to the financial risks taken on. The investor's personality refers to the stable characteristics an individual tends to display in any given situation. Personality traits may therefore also be considered as a driver in investor financial decisions. Understanding the influence gender and personality traits have on an investor's financial risk tolerance, will assist in predicting their financial and investment decisions with regards to their asset portfolios. The purpose of this article is to develop a structural equation model for investment firms to more accurately profile their female investors, considering their personality traits, level of risk tolerance and level of education. Results from this study are in line with previous investment and portfolio management research. Results indicate that male investors are more risk-tolerant than their female counterparts. Furthermore, investors' level of education significantly influenced their level of financial risk tolerance. Personality traits were found to influence female investors financial risk tolerance.
Keywords: G23; G41; J16; 330; education; female investor; gender; personality traits; risk tolerance; structural equation model